Detection of a hydrogen sulfide-negative Salmonella Typhimurium from cattle feces in a cross-sectional study of cow–calf herds in the Southeastern United States - Bentum, Kingsley E.; Kuufire, Emmanuel; Nyarku, Rejoice; Woods, Chase; Ale, Khim; McKie, Luis; McKenzie, David; Jackson, Charlene R.; Adesiyun, Abiodun; Opoku-Agyemang, Tony; Samuel, Temesgen; Reddy, Gopal; et al. (Frontiers in Veterinary Science, 2025)
IntroductionCattle are well-recognized reservoirs of Salmonella; however, reports of atypical hydrogen sulfide (H2S)-negative strains from bovine sources remain scarce. This cross-sectional study aimed to investigate the antimicrobial resistance profiles and epidemiology of Salmonella among rural cow-calf herds in Alabama, United States, with a particular focus on isolating emerging H2S-negative variants.MethodBetween April and May 2024, a total of 311 fecal samples were collected from cattle across 18 farm operations in six counties. Samples were cultured for Salmonella, and recovered isolates were identified using whole genome sequencing and the Salmonella In Silico Typing Resource. H2S production was assessed using Xylose Lysine Deoxycholate agar, Lysine Iron Agar, and Triple Sugar Iron agar. Antimicrobial susceptibility testing was performed against 24 antimicrobial agents. A mixed-effects logistic regression model was used for statistical analysis.ResultsOverall, 3.5% (11 out of 311) of animals from 27.8% (5 out of 18) of the farms tested positive for Salmonella. Fifteen isolates representing six serovars were identified: Salmonella Thompson (5 out of 15), Salmonella Hadar (4 out of 15), Salmonella Braenderup (3 out of 15), Salmonella Enteritidis (1 out of 15), Salmonella Bareilly (1 out of 15), and Salmonella Typhimurium (1 out of 15). Notably, the tet(A) gene conferring tetracycline resistance was detected exclusively in the Salmonella Hadar isolates. Diarrheic animals were significantly more likely to shed Salmonella in their feces (p value = 0.0192). Importantly, the Salmonella Typhimurium isolate was identified as an H2S-negative strain, carrying an A > C missense mutation in the phsC gene and a C > T synonymous mutation in the cysI gene.ConclusionTo our knowledge, this is the first report of an H2S-negative Salmonella Typhimurium isolate from cattle feces. These findings also reveal a notable prevalence of Salmonella shedding among an underexplored population of rural cow-calf herds in the southeastern United States. The potential public health implications of these findings merit further investigation.